Islam in Bangladesh politics: the role of Ghulam Azam of Jamaat-I-Islami - Hossain, Ishtiaq; Siddiquee, Noor Alam (Taylor & Francis, London, UK, 2006)
In recent years, Islam has emerged dramatically in the politics and news headlines of the world. As elsewhere in the Muslim World, the impact of the Islamic resurgence movement is clearly visible in contemporary Bangladesh. Organized and led by Ghulam Azam until very recently, the Jamaat is now the largest and most active Islam-based political party in Bangladesh. This paper attempts to analyse the politics of Jamaat, with reference to Ghulam Azam and his political ideas and thought. First, this paper attempts to put Jamaat-I-Islami within the context of Bangladesh politics. We then provide a short biographical sketch of Ghulam Azam, showing his exposure to both Western and Islamic educations and their impact on his political activities. This paper next focuses on some of his political ideas and contributions and analyses them in the light of contemporary socio-political realities in Bangladesh, demonstrating the signiﬁcant and controversial impact of his political activism and strategies on contemporary Bangladesh politics and society. The paper concludes that neither Ghulam Azam nor his party has been able to change generally negative perception about Jamaat and thus signiﬁcantly widen its acceptance among the masses. Rather, at times, comments of Jamaat leadership like ‘we did no mistakes in 1971’ have infuriated the nationalist and patriotic forces and widened the gap between Jamaat and common people. It remains to be seen how Ghulam Azam and the new Jamaat leadership tackle these challenges in future.